THE RELATIONSHIP OF KNOWLEDGE ATTITUDE AND DIETARY COMPLIANCE WITH BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS IN THE INTERNAL DISEASE CLINIC OF VITA - Arsiaty; Yulia Delfahedah (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
Diabetes Mellitus (DM) is a chronic metabolic disorder caused by impaired insulin secretion, insulin resistance, or a combination of both. Controlling blood sugar levels is the main thing for DM sufferers, one of which is with diet/nutrition therapy. Correct diet therapy is based on basic knowledge and attitudes. good for controlling blood sugar This study aims to determine the relationship between knowledge, attitudes and dietary compliance with blood sugar levels in DM patients at the Internal Medicine Polyclinic at Vita Insan Hospital in 2019. This research is an analytic study with a cross-sectional design, carried out from July 2019. the sample used a purposive sampling technique consisting of 52 DM patients. The data taken included aspects of knowledge, attitudes.diet adherence (primary) and blood sugar levels (secondary) Computerized data processing using Chi Square test Univariate analysis results showed 69.2% of patients had uncontrolled blood sugar levels, 59.6% of patients had insufficient knowledge but 59.6% patients had a positive attitude towards efforts to control blood sugar and 53.8% of patients were disobedient to the diet given. From Bivariate analysis there was a significant relationship between knowledge, dietary adherence and blood sugar levels (p<0.05), but for attitudes there was no significant relationship (p-0.05) Suggestions for health workers to further improve patient understanding of the DM diet so that patient's blood sugar levels are controlled by providing education and developing information provision,for the family it is necessary to provide support and motivation so that the patient is on a diet.